Multifocal metalens for detecting several topological charges at different wavelengths - A.G. Nalimov; V.V. Kotlyar (Компьютерная оптика, 2023)
A combined high-aperture metalens in a thin silicon nitride film, which consists of two inclined sector metalens, is considered. Each sector metalens consists of a set of binary subwavelength gratings. The diameter of the lens is 14 μm. It has been shown using time-domain finite difference method that the metalens can simultaneously detect optical vortices with two topological charges –1 and –2, in almost the entire visible wavelength range. The metalens can distinguish several wavelengths that are focused at different points in the focal plane: a 1 nm change in wavelength results in a focal spot shift of about 4 nm. When the metalens is illuminated by a Gaussian beam with left-handed circular polarization, two optical vortices with topological charges 1 and 2 are simultaneously formed at 6 nm between each other at focal distance equals 6 nm. This metalens can be used to increase information in transmission channel in wireless telecommunication systems by selecting the space-time modes of laser radiation with different topological charges and different wavelengths. The considered microlens is an example of a compact demultiplexer.